THE IMPACT OF UNDERSTANDING OF THE COMBINED OPERATING DOCTRINE FOR ALKI-I SECURITY OPERATIONS - Setiawan, Erick Budi (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2019)
Indonesia is one of the archipelagic states in the world that has a very important role for international shipping, so there is a need for security controls to maintain the sovereignty of the territorial waters of the Republic of Indonesia by providing 3 shipping lines that can be passed by ships from other countries to be able to cross through the archipelagic sea lane. One of them is ALKI-I which crosses the Natuna Sea, Karimata Strait, Java Sea, and Sunda Strait. One of the joint operations carried out by the TNI to anticipate all forms of violations and threats in ALKI-I is the ALKI-I Security Operation. The main theory used in the discussion of this research is the Interoperability theory, supported by several theories including integration theory, system theory, theory coordination, and security theory. This research uses an explanative qualitative approach using Nvivo Software for processing data obtained from in-depth interviews with operations executors. The results of the analysis conducted using the Miles, Huberman and Saldana models found that the impact caused by the problem was that the operation was not yet effective and efficient. Keywords: ALKI-I Security Operation, Interoperability Theory, Miles Huberman and Saldana models analysis, NVivo Software, The Doctrine Of Joint Operations